Mechanical determinants of acceleration and maximal sprinting speed in highly trained young soccer players - Buchheit, M.; Samozino, P.; Glynn, J. A.; Michael, B. S.; Al Haddad, H.; Mendez-Villanueva, A.; Morin, J.-B. (Journal of Sports Sciences, 2014)
The aim of the present study was to examine, in highly trained young soccer players, the mechanical horizontal determinants of acceleration (Acc) and maximal sprinting speed (MSS). Eighty-six players (14.1 ± 2.4 year) performed a 40-m sprint to assess Acc and MSS. Speed was measured with a 100-Hz radar, and theoretical maximal velocity (V0), horizontal force (F0) and horizontal power (Pmax) were calculated. Within each age group, players were classified as high Acc/fast MSS (>2% faster than group mean), medium (between -2% and +2%), and low/slow (>2% slower). Acc and MSS were very largely correlated (-0.79; 90% confidence limit [-0.85; -0.71]). The determinants (multiple regression r2 = 0.84 [0.78; 0.89]) of Acc were V0 (partial r: 0.80 [0.72; 0.86]) and F0 (0.57 [0.44; 0.68]); those of MSS (r2 = 0.96 [0.94; 0.97]) were V0 (0.96 [0.94; 0.97]) and Pmax (0.73 [0.63; -0.80]). High/Med have likely greater F0 (Cohen`s d: +0.8 [0.0; 1.5]), V0 (+0.6 [-0.1; 1.3]) and Pmax (+0.9 [0.2; 1.7]) than Low/Med. High/Fast have an almost certainly faster V0 (+2.1 [1.5; 2.7]) and a likely greater Pmax (+0.6 [-0.1; 1.3]) than High/Med, with no clear differences in F0 (-0.0 [-0.7; 0.6]). Speed may be a generic quality, but the mechanical horizontal determinants of Acc and MSS differ. While maximal speed training may improve both Acc and MSS, improving horizontal force production capability may be efficient to enhance sprinting performance over short distances.